Analisis Hak-Hak Buruh Pabrik Dalam Syariat Islam - Syahira, Nazwa; Azizah, Zhulfi Laily (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This research is entitled "Analysis of Factory Workers' Rights in Islamic Law". This study aims to find out what rights and obligations must be accepted by workers in Islamic law and whether workers' rights to factory companies are fulfilled according to Islamic law. This study uses a qualitative analysis method by understanding and formalizing the data systematically. The result of this research is how workers cover the basic rights of workers. This includes the right to fair and decent wages, reasonable working hours, safe and healthy working conditions, and the right to organize and strike as a form of protest. This abstract underscores the importance of understanding and analyzing labor matters in the context of labor law and economics. In this era of globalization and rapid technological change, it is important to keep updating and reviewing labor materials to suit the demands and changes in the world of work. Thus, further research in this area will make a significant contribution to strengthening the protection and well-being of workers in the future.